THE MANIFESTATION OF THE STANDARD OF 19 TH CENTURY IDEAL WOMAN IN BRITAIN PRESENTED BY SARA IN BURNETT'S A LITTLE PRINCESS - KURNIAWATI, DESI EKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Feminism, Patriarchal, Standards of 19th Century Ideal WomenWomen emancipation is not a new issue. Nowadays, people see that women have more freedom to express themselves, especially in deciding their life path. However, that opinion is not completely right because actually women are still trapped by the society’s rules on how women should be. Those rules control women so they can be ideal ones, based on had their freedom, but women’s subservience to the society’s rules is not easy to be erased. They will follow the society’s expectations consciously or not. This phenomenon has happened since a long ago. For the analysis, the writer uses a novel entitle A Little Princess by Frances Hudgson Burnett as the object of analysis. This novel tells the reader about the efforts of young girl named Sara Crew to fulfill the standards of 19th century ideal women in Britain. Therefore, the writer makes a problem of the study, of the thesis is how Sara as the main character in A Little Princess manifests the standards of ideal woman in 19th century in Britain.The study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Descriptive study in textual analysis is applied in this study to analyze the relation between the statements of Sara Crew in the novel and the ideal women standards she wants to reach.The result of this study shows the efforts of Sara Crew as the main character in fulfilling the standards of 19th century ideal women had created her on ideal women in the society. She successfully fulfills those standards in every condition. Those standards control women to be piety, patient, frugal, and industry.The writer suggests English Department students to analyze the 19th century standards of ideal women in Britain by using different object. The nextresearcher can also find an object which has different theme from this analysis.